2004
DOI: 10.1002/ijc.20757
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes: A new delivery system for tumor antigens in cancer immunotherapy

Abstract: Exosomes are small membrane vesicles that are released into the extracellular environment during fusion of multivesicular bodies with plasma membrane. Exosomes are secreted by various cell types including hematopoietic cells, normal epithelial cells and even some tumor cells. They are known to carry MHC class I, various costimulatory molecules and some tetraspanins. Recent studies have shown the potential of using native exosomes as immunologic stimulants. Here, we demonstrate a novel means of using exosomes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
126
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(126 citation statements)
references
References 44 publications
0
126
0
Order By: Relevance
“…To alleviate the negative effects as well as to increase the anti-tumor effects, it is necessary to develop an innovative method for tumor-derived exosomes. Previously, we have reported improved anti-tumor effects of manipulated tumor-derived exosomes by enrichment with human tumor antigen MUC-1 and Hsp70 that efficiently suppressed tumor growth (Cho et al, 2005(Cho et al, , 2009). Therefore, tumor-derived exosomes-based immunotherapy needs to be modified to increase therapeutic efficacy and enhance immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To alleviate the negative effects as well as to increase the anti-tumor effects, it is necessary to develop an innovative method for tumor-derived exosomes. Previously, we have reported improved anti-tumor effects of manipulated tumor-derived exosomes by enrichment with human tumor antigen MUC-1 and Hsp70 that efficiently suppressed tumor growth (Cho et al, 2005(Cho et al, , 2009). Therefore, tumor-derived exosomes-based immunotherapy needs to be modified to increase therapeutic efficacy and enhance immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-derived exosomes contain tumor-specific antigens and tumor peptide/ MHC class I complexes that can prime tumor-specific CTLs and can elicit a potent tumor-specific immune response (Wolfers et al, 2001). Malignant effusions accumulate exosomes bearing tumor antigens and antigenpresenting molecules that can generate anti-tumor T cell responses (Andre et al, 2002), and exosomes from different tumor cells showed that exosomes prohibited not only syngeneic but also allogeneic tumor growth (Andre et al, 2002;Cho et al, 2005). These studies provide a rationale that tumor-derived exosomes have the potential as an efficient cell-free therapeutic vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Full-length human MUC1 (MUC1) expression using a retroviral construction was prepared, as described previously (Cho et al, 2005). Supernatants that contain MUC1 encoding retroviral particles were transduced into MDA-MB-231 and T47D human breast adenocarcinoma cell lines.…”
Section: Transfectionmentioning
confidence: 99%
“…Zitvogel et al (3) first demonstrated vaccination of DC-derived EXO in eradication of tumors in animal models. Subsequently, EXO-based vaccines have been confirmed to stimulate strong CTL responses and induce antitumor immunity in different animal models (6,7). However, its therapeutic efficiency is still limited to only production of prophylactic immunity against tumors possibly due to lacking capacity of breaking immune tolerance (8).…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%